Providing of Condition to Compare Animal Sperm Cryopreservation Results - Gorbunov, L. V. (Problems of Cryobiology and Cryomedicine, 2011)
The method for analysis of thawed animals’ sperm, providing the comparability of the obtained results when working with ejaculates of different motilities has been proposed. The rise has been established in the reproducibility of the experimental results up to 4.5 times if compared with the existing analogues. Comparative analysis based on different estimation criteria of the differences of cryopreservation results for animals’ sperm has shown that when using the proposed way of biometrical processing with the reliability level of 0.95 the amount of ejaculate is minimum expendable.